Investigation of Draft-Gear Energy Absorption Capacity Effect on the Dynamic Structural Behavior of the Freight Cars’ Supporting Structures - V. I. Belyaev; D. A. Stupin; V. S. Plotkin; A. N. Stepanov (Вестник Научно-исследовательского института железнодорожного транспорта, 2015)
The paper tackles the protection problem of freight cars carrying hazardous materials while being solved through use of coupler center draft gears with increased energy absorption capacity. It is demonstrated that the adopted commodity-based classification of draft gears, eligible under different energy absorption capacity requirements, ensures more reliable protection and prevention of hazards in possible emergency situations involving such cars. The method is put forward allowing for quantitative evaluation of the draft gear energy absorption capacity influence on the reduction in forces acting upon a freight car as well as on the car damageability degree in operation under emergency conditions and increase in the bearing members remaining life expectancy of the car body structure. There are presented results of the impact tests of freight cars equipped with draft gears having various energy absorption capacity added with the outcomes of these results based car loading calculations. The tests confirmed that freight car equipping with draft gears having extended energy absorption capacity contributes to considerable increase in the life time expectancy of freight car structure and increase in the safe impact speeds at which the level of forces does not exceed the car strength level (thus reducing the probability of contingencies and accident severity as well).